THEORETICAL AND ANALYTICAL FOUNDATIONS OF THE FUNCTIONING OF UKRAINE’S AGRICULTURAL SECTOR AND ASSESSMENT OF THE ACTIVITIES OF AGRICULTURAL PRODUCERS (INNOVATIVE ECONOMY, 2026)
Ivchenko V.M. Theoretical and Analytical Foundations of the Functioning of Ukraine’s Agricultural Sector and Assessment of the Activities of Agricultural ProducersPurpose. The aim of the article is to review the role of rural households in the structure of the agricultural sector of the Ukrainian economy in modern conditions, in particular their contribution to the production of gross agricultural products, ensuring domestic food security, and forming the export potential of agri-food products.Methodology of research. Framework is based on general scientific and specialized research methods, including analysis and synthesis of statistical data, comparative analysis of production and export dynamics, a structural-functional approach to assessing the role of different categories of farms, and methods of generalization and systematization of analytical information. The information base consists of official statistical data and sectoral analytical reports.Findings. The study reveals that the structure of gross agricultural output remains disproportionate: crop production accounts for approximately 70%, while livestock production represents 30%. A decline in the cattle population (by 8% in 2025) indicates crisis tendencies in the livestock sector. Agricultural enterprises generate 55% of gross output, farms account for 17%, and rural households contribute 28%, reflecting a clear functional differentiation among producer categories.Changes in the export structure have been identified: the role of oilseed crops and processed oilseed products, as well as sugar, is increasing, while the share of traditional cereals in foreign currency revenues is gradually decreasing. The European Union is strengthening its position as a key market for Ukrainian agricultural exports, particularly in the segments of rapeseed, sunflower seeds, and vegetable oils.Originality. A comprehensive generalization of structural changes in the agrarian sector of Ukraine, occurring in the conditions of a war economy and simultaneous deepening of European integration processes, is substantiated, which allows for a systematic description of the transformation of the industry structure of production, the redistribution of resources and the change in priorities for the development of the agrarian sector. New export trends in the Ukrainian agrarian sector are also identified, in particular, the strengthening of the role of oilseeds in the structure of agricultural exports and the gradual growth of the share of products with higher added value, which indicates a reorientation of the export model from raw materials to a more diversified and processing-oriented one.Practical value. The obtained results lie in their potential use for shaping state agricultural policy, developing livestock support programs, stimulating the processing industry, and enhancing the country’s export potential. The results may also be applied in academic research, educational activities, and analytical work of public administration bodies.Key words: agricultural sector of Ukraine, agriculture, crop production, livestock production, agricultural exports, food security, European integration, structural transformations, rural households.
Keywords: agricultural sector of Ukraine; agriculture; crop production; livestock production; agricultural exports; food security; European integration; structural transformations; rural households